Risk evaluation of tailings dam based on game theory and matter-extension theory - Song Huaqiang; Wang Guan; Luo Tian; Yang Zongda; Xu Jingyuan; Jiang Wei (E3S Web of Conferences, 2022)
The safety and stability of tailings dam are directly related to the safety of life and property of downstream residents and the ecological and environmental safety of downstream rivers and farmland. During the operation stage of the tailings pond, safety assessment shall be carried out from seepage damage of the tailings dam, instability of the dam foundation, structural damage of the dam body, flooded roof, and safety management, etc. Aiming at a tailings pond in the running stage of Guangxi Province in China, by establishing the evaluation index system and its grading standard of the tailings dam-break, the subjectivity and objectivity of the evaluation index are taken into consideration by the combination of matter-element extension theory and game theory. Meanwhile, in order to solve the problem of the defect of the correlation function when the eigenvalue exceeds the controlled field and of the incommensurability for different units, a linear dimensionless method is adopted. The results show that the grade of tailings dam-break is I, and the eigenvalue of grade variable is 1.3, that is, the tailings pond is a “normal tailing reservoir”, but there is a risk of evolution to the “sickness tailing reservoir”. Thus, corresponding measures must be taken to prevent. In addition, the result of the two methods is consistent by comparing with the unascertained measure method, which not only validates the accuracy of the evaluation method, but also embodies the unique advantage of possessing the eigenvalue of grade variable to alert its evolution direction.